Clinical Characteristics and Drug Susceptibility Profiling of Multidrug-Resistant Pseudomonas aeruginosa Infections - Mingxia Cai; Zhibin Zhou; Jiaming Huang; Yuxia Du (International Journal of Clinical Practice)
Conclusion: Male patients with hemiplegia should be closely monitored for MDR-PA infections when PA is detected. Mechanical ventilation necessitates vigilance against DTR-PA. Aminoglycoside-based combination therapy offers an effective empirical option for resistant PA infections. These findings indicate the need for antimicrobial stewardship or infection control measures to address MDR-PA and DTR-PA infections.